Integrative Empowerment Intervention of Community Health Workers In Controlling Non-Communicable Diseases (NCDs) With A Herbal- Based Local Wisdom Approach - Cahyaningrum, Ika Cahyaningrum; Ka'arayeno, Arie Jefri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Promotional and preventive efforts are very important in combating non-communicable diseases (NCDs), including through the use of traditional medicines. Given the public's limited knowledge about the safe and effective use of natural ingredients, it is essential to raise awareness about the types, processing, and proper consumption of medicinal plants. Community health workers, as the frontline of primary health care, play a particularly important role in disseminating this information. The purpose of this study was to analyze the effect of applying an integrative empowerment model on the ability of community health workers to control NCDs with an herbal-based local wisdom approach. The research method used was a pre-experimental experiment with one group pretest-posttest design. Researchers applied an empowerment model with a meeting duration of 200 minutes. The sample of this study consisted of 57 community health workers in the Wagir community health center, using consecutive sampling techniques. The results showed a significant effect of applying the integrative empowerment model on the knowledge and skills of community health workers in controlling NCDs with an herbal-based local wisdom approach in the Wagir community health center with a p value (0.001) with a difference in the mean knowledge and skills of 15,228 and 46,632, respectively. This study concluded that there was a significant effect of applying the integrative empowerment model on the knowledge and skills of community health workers in controlling NCDs with an herbal-based local wisdom approach.